Polymorphisms in ERCC1 and XPF Genes and Risk of Gastric Cancer in an Eastern Chinese Population - He, Jing (Public Library of Science, 2012)
BACKGROUND: Inherited functional single nucleotide polymorphisms (SNPs) in DNA repair genes may alter DNA repair capacity and thus contribute to cancer risk. METHODS: Three ERCC1 functional SNPs (rs2298881C>A, rs3212986C>A and rs11615G>A) and two XPF/ERCC4 functional SNPs (rs2276466C>G and rs6498486A>C) were genotyped for 1125 gastric adenocarcinoma cases and 1196 cancer-free controls by Taqman assays. Odds ratios (OR) and 95% confidence intervals (CI) were used to estimate risk associations, and false-positive report probabilities (FPRP) were calculated for assessing significant findings. RESULTS: ERCC1 rs2298881C and rs11615A variant genotypes were associated with increased gastric cancer risk (adjusted OR = 1.33, 95% CI = 1.05–1.67 for rs2298881 AC/CC and adjusted OR = 1.23, 95% CI = 1.05–1.46 for rs11615 AG/AA, compared with their common genotype AA and GG, respectively). Patients with 2–3 ERCC1 risk genotypes had significant increased risk (adjusted OR = 1.56, 95% CI = 1.27–1.93), compared with those with 0–1 ERCC1 risk genotypes, and this risk was more significantly in subgroups of never drinkers, non-gastric cardia adenocarcinoma (NGCA) and clinical stage I+II. All these risks were not observed for XPF SNPs. CONCLUSIONS: These findings suggest that functional ERCC1 SNPs may contribute to risk of gastric cancer. Larger and well-designed studies with different ethnic populations are needed to validate our findings.